PENATAAN PASAR RAKYAT DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2019 - Irma Yani Bangun; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The people’s market is one of the most basic forms of populist economic application. Structuring becomes part of a process of government implementation that in the process of structuring can guarantee the realization of national development goals. Pekanbaru City Regulation No. 9 of 2014 concerning the management of the people’s market, Structuring is an effort made by the Local Government to organize and organize the existence and establishment of people’s markets, shopping centers and convenience stores in an area so that each one develops harmoniously, mutually beneficial and strengthens each other. Simpang Baru Panam Market is one of the markets in Tampan Subdistrict that received special allocation fund assistance in fiscal year 2019.This research aims to describe the arrangement of the people’s market in Simpang Baru Panam Pekanbaru market in 2019. This study uses a qualitative approach. Research location in Pasar Simpang Baru Panam Pekanbaru City. The data sources in this study are informants and document. The method used in this study is descriptive research with qualitative approach. Research data types are primary and secondary data. The data collection technique in this study are documentation and interviews. The data analysis technique used in qualitative data analysis.The results of this study show that the market arrangement there are 3 stages, namely,planning in market development, Mobilization in market arrangement, and Supervision in the market. Planning as the basis of thinking of the objectives and the preparation of measures that will be used to achieve the objectives in the structuring of the market in terms of physical condition of the building. Furthermore, the mobilization, which is meant to move all resources in the organization so that the work and activities carried out can achieve the objectives in the market. And supervision is given to Simpang Baru Market to improve security and order on the market. Factors that influence market stucturing are, budget structuring in market development, and human resources. Keywords : Structuring, Development, and Simpang Baru Market.